2014
DOI: 10.3109/13880209.2013.874536
|View full text |Cite
|
Sign up to set email alerts
|

Consumption ofCoprinus comatuspolysaccharide extract causes recovery of alcoholic liver damage in rats

Abstract: Context: Excess use of alcohol is known to be associated with liver diseases such as fatty liver, alcoholic hepatitis, and cirrhosis. Various practices may be applied to prevent or treat the damage caused by chronic alcoholism. Coprinus comatus (O.F. Mü ll.) Pers. (Agaricaceae) is a macrofungus that has been reported to aid the recovery of murine livers damaged by benzopyrene. Objective: In this study, the possible therapeutic effects of three different doses (50, 100, and 150 mg/kg) of C. comatus polysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Seven day treatment with aqueous A c c e p t e d M a n u s c r i p t 13 peroxidation intensity in a statistically significant manner and also showed prevention of histological changes in liver cross sections (91) . A recent study of Ozalp et al, (2014) has shown that daily administration of 50 mg/kg of C. comatus polysaccharides extract considerably reduced the negative effects of alcohol on rat liver (92) .…”
Section: Coprinus Comatus (Family: Agaricaceae)mentioning
confidence: 98%
“…Seven day treatment with aqueous A c c e p t e d M a n u s c r i p t 13 peroxidation intensity in a statistically significant manner and also showed prevention of histological changes in liver cross sections (91) . A recent study of Ozalp et al, (2014) has shown that daily administration of 50 mg/kg of C. comatus polysaccharides extract considerably reduced the negative effects of alcohol on rat liver (92) .…”
Section: Coprinus Comatus (Family: Agaricaceae)mentioning
confidence: 98%
“…investigated the hypoglycaemic, hypolipidaemic, and antioxidant activities of mycelia selenium-polysaccharides and the hepatoprotective activities of fruiting body polysaccharides from C . comatus , respectively 14 , 15 . However, previous research on C .…”
Section: Introductionmentioning
confidence: 97%
“…The fruiting bodies of T. albuminosus are composed of bioactive components, such as polysaccharides, proteins, amino acids, lipids, ergosterol, saponins, cerebrosides, hydrogen peroxide-dependent phenol oxidase, alkaline protease, coumarin and melanin, which are used to strengthen peristaltic ability and in the treatment of some diseases, including intestinal carcinoma, hemorrhoids, hyperlipidemia, hyperglycemia, and antioxidant and antimicrobial diseases [10,11,12,13,14,15,16]. Among these bioactive components, polysaccharides have attracted increasing attention due to their antioxidant, immunomodulating, hepatoprotective, and anti-inflammatory biological activities [11,17,18]. Because the T. albuminosus fruiting body cannot be artificially cultivated, T. albuminosus mycelia are easily obtained by submerged fermentation, which is a rapid and alternative method.…”
Section: Introductionmentioning
confidence: 99%